Women's Language Features in Jo March’s Dialogues from Little Women Movie - Ainurisanti, Ragilisna Dwi (Universitas Negeri Malang, 2023)
This research explores the language features of women in the dialogues of Jo March from the Little Women movie using a sociolinguistic approach to identify the language features applied by the main character to understand the social factors and dimensions influencing women's language using the theory of women's language features proposed by Robin Lakoff. A qualitative descriptive method was used to analyze the data and direct observation of the film. Eight types of women's language features were found in the Little Women movie, along with several social factors influencing the language used by the main character, such as participants, background, topic, and function. The social factors of each feature are closely related to their usage context, in addition to the social dimensions associated with the analysis factors consisting of social distance, status, formality, and function. Keywords: women language; gender; social dimensions; sociolinguistics Fitur Bahasa Wanita dalam Dialog Jo March dari Film Little Women Penelitian ini mengeksplorasi fitur bahasa wanita dalam dialog Jo March dari film Little Women dengan menggunakan pendekatan sosiolinguistik yang bertujuan untuk mengidentifikasi fitur bahasa yang diterapkan oleh karakter utama untuk mengetahui faktor dan dimensi sosial yang mempengaruhi bahasa wanita menggunakan teori fitur bahasa wanita yang dikemukakan oleh Robin Lakoff. Metode deskriptif kualitatif digunakan untuk menganalisis data dan observasi langsung terhadap film. Terdapat delapan jenis fitur bahasa wanita yang ditemukan dalam film Little Women dan beberapa faktor sosial yang mempengaruhi bahasa perempuan yang digunakan oleh tokoh utama, seperti partisipan, latar, topik, dan fungsinya. Faktor sosial dari setiap jenis fitur terkait erat dengan konteks penggunaannya selain dimensi sosial yang terkait dengan faktor analisis yang terdiri dari jarak sosial, status, formalitas, dan fungsi. Kata kunci: bahasa wanita, gender, dimensi sosial, sosiolinguistik